ТЕОРЕТИЧЕСКИЕ ОСНОВЫ ПОДГОТОВКИ МЕНЕДЖЕРОВ ОБРАЗОВАНИЯ - Цинивский, Илья; Алексин, Юрий (Modern scientific researches, 2019)
In this article the theoretical bases of training of managers of education were considered, their professional competence and principles of the development of the content of vocational education were outlined. Integration of Ukraine into the world communi